Population dynamics and CPUE of Alosa genus with emphasis on Alosa braschnikovi (Borodin, 1904) on the coasts of Golestan Province, Iran - ZOBEYDE BIBAK; SEYYED YOUSEF PAIGHAMBARI; MOJTABA POULADI; RASOUL GHORBANI; SEYYED ABBAS HOSSEINI; MOHSEN YAHYAEI (Biodiversitas Journal of Biological Diversity, 2018)
Bibak Z, Paighambari SY, Pouladi M, Ghorbani R, Hosseini SA, Yahyaei M. 2018. Population dynamics and CPUE of Alosa genus with emphasis on Alosa braschnikovi (Borodin, 1904) on the coasts of Golestan Province, Iran. Biodiversitas 19: 59-66. The aim of this study was to compare relative abundance and catch per unit effort of members of the Alosa genus (family: Clupeidae) in the fishing grounds of Gomishan and Miankale in Golestan coasts. Sampling operations were done by beach seine during 2011 to 2012. A total of 240 fish were collected. Identified species in Gomishan were: Alosa braschnikovi (Borodin, 1904) and A. saposchnikovi (Grimm, 1887). The most abundant species in this region were individuals of A. braschnikovi. The highest length and weight in the region were 35.6±1.85 mm and 447.8±57.43 gr for Alosa braschnikovi in Gomishan. Besides the two mentioned species, A. kessleri (Grimm, 1887) was caught in Miankale coasts. The most abundant species again was Alosa braschnikovi in this region. The highest length and weight were 33.12±3.18 cm and 362.5±99.57 gr for Alosa braschnikovi in Miankale region. The results showed that mean of CPUE in Miankale was higher than in the Gomishan region. The comparison of sex ratio for shads showed that males were dominant against females. Also, the comparison between species showed that the highest values for length, and weight of fish species compared belonged to Alosa braschnikovi. Among the Alosa braschnikovi fishes caught, individuals were in the range of 2 to 5 age groups within the two compared regions and most abundant were observed in 4 age groups.